Changes in the Characteristics of American Youth: Implications for Adult Outcomes - Altonji, Joseph G.; Bharadwaj, Prashant; Lange, Fabian (Journal of Labor Economics, 2012)
We examine changes in the characteristics of American youth between the late 1970s and the late 1990s, with a focus on characteristics that matter for labor market success. The current generation is more skilled than the previous one. Blacks and Hispanics have gained relative to whites, and women have gained relative to men. However, the skill distribution has widened overall. Shifts in parental education generate many of the observed changes. We also provide speculative estimates suggesting that if recent trends in technology and the supply of human capital continue, wage inequality will increase substantially by 2025.